When Club Culture Goes Online: The Case of Boiler Room - Guillaume Heuguet (Dancecult: Journal of Electronic Dance Music Culture, 2016)
Contemporary media technologies are often perceived as providing an opportunity to widen the audiences of cultural events. Online video broadcast (“streaming”) formats seem to be especially promising for popular music events. This article analyzes the encounter between these club/rave culture and streaming technology through a dual event—both on-site and mediatized—run by a [relatively] new organization, Boiler Room. Video streaming seems to offer the promise of alleviating many obstacles to participation historically associated with underground culture, but in doing so it also threatens to undermine the specialist exclusivity that contributes to the community’s own sense of authenticity. This article is interested in how event organizers appropriate such technologies, adjusting them to club culture in order to develop online an original variant of the DJ experience.  We aim to show how decisions regarding stage design, videography, and website development all contribute to building the social significance and specificity of an episode in club culture.